Text Messages Based Interventions for Pregnant Women's Health: Systematic Review - SEZER BALCI, AYŞE; KADIOĞLU, HASİBE (MARMARA UNIV, INST HEALTH SCIENCES, 2019)
Objective: The aim of this systematic review was to summarize evidence for the effectiveness of text message-based randomized controlled studies for the health of pregnant women. Methods: We searched the following databases from 2005 and 2015, using databases Google Scholar, Pubmed, Ovid, Cochrane Library. The question of this systematic review

what are results of text message-based interventions on the health of pregnant women? Total of 15 articles was received that met the inclusion criteria for the study. After each full article was read, fifteen articles were included in this review. Results: Text message were effective on smoking cessation, weight control, diabetes management, motherhood readiness, developing negative attitudes towards alcohol consumption. Conclusion: This systematic review suggests use of text message is more practical and cost-effective method for promoting the health of pregnant women and they had a positive effect on health practices of pregnant women.
Keywords: health applications; mobile health; pregnant women; primary care; text message; INFLUENZA VACCINATION; SMS; PREVENTION; TEXT4BABY; TRIAL; PHONE